Susceptibility profiles and resistance genes for carbapenems (cfiA) and metronidazole (nim) among Bacteroides species in a Turkish University Hospital - ÜLGER, NURVER (ELSEVIER SCI LTD, 2012)
Sixty-six nonduplicate Bacteroides clinical isolates collected at Marmara University Hospital were tested to investigate carbapenem and metronidazole resistance profiles and to detect the resistance genes (cfiA and nim) and related insertion sequence (IS) elements. The study found that there were no strains resistant to metronidazole and nim genes were not detected in any of the strains. Five Bacteroides fragilis strains were resistant to meropenem, one of which was also resistant to imipenem. The cfiA gene was detected in 27% of strains, 32% of strains had the IS 1187 element, and five strains harbored both gene cfiA and IS 1187. These results indicate higher rates of carriage of the cfiA gene and IS1187 insertion elements than have been reported in other countries. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Bacteroides fragilis; Carbapenem; Metronidazole; Antimicrobial resistance; IS elements; DNA-SEQUENCE; FRAGILIS; INSERTION; IDENTIFICATION; PREVALENCE; EXPRESSION; UPSTREAM